Performance Analysis of Hybrid Photovoltaic Thermal (PV/T) Solar Collector by Varying PV Panel and Cooling of Glass Cover: Improving Efficiency of Hybrid Photovoltaic Thermal Solar Collector with Cooling and Film Type Water Cooling (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Photovoltaic cells suffer from a drop in efficiency with the rise in temperature due to increased resistance Such systems can be engineered to carry heat away from the PV cells thereby cooling the cells and thus improving their efficiency by lowering resistance. Although this is an effective method, it causes the thermal component to under-perform compared to a thermal collector. Recent research showed that photovoltaic materials with low temperature coefficients. Integration of photovoltaic panel and solar thermal technologies into one single solar energy device, with dual generation of electricity and heat energy. The main aim of this research work is to improve the overall efficiency by the film type water cooling on the collector glass cover and also the take the performance of the PV panel is suitable for this system have to choose. Hence, solar collectors fabricated from locally available materials and tested in climate conditions of GIT Campus. Various parameters like isolation, temperatures at various locations, voltage, and current measured with help of calibrated Instruments.Result shows that, integration of Hybrid solar collector with Poly Crystalline panel gives more performance compared with hybrid solar collector with Mono crystalline panel. Reason behind the performance is with poly crystalline thermal efficiency and electrical efficiency increased rather than mono crystalline used in hybrid solar collector. Here the over efficiency gives the poly crystalline is 5.11 increased rather than used the mono crystalline, Also, another result shows that when the cooling apply over the glass cover of the hybrid solar collector the overall efficiency increased 12.46 compared with without cooling of glass cover.